The Nahwu Learning with Insya’ Bi Al-Anmath Method: The Case of One Arabic Language Department - Ahmad Fikri (Ta'dib: Jurnal Pendidikan Islam, 2017)
This research was driven by the fact that the discovery of phenomenon of student's difficulties and low ability of qowa`id in Nahwu subject, especially with regard to the method of learning used by the lecturers and the students. Due to such a phenomenon, I tried to use the method of Insya` bi Al-Anmath as an alternative solution to be able to grow up students’ interest, spirit, and motivation and improve the students’ Nahwu ability. The participants of this study were the third semester students who took Nahwu I as the subject of the course. This study used the action research method by implementing Insya `bil Al-Anmath method. Observation, interviews, and tests were used to collect the data. Based on the result of the research, the researcher found that the learning method, Insya` bil Al-Anmath in the process of learning Nahwu could improve the quality of the learning process, students’ interest and the academic output of Nahwu students.